The position of digital citizenship education in the official curricula of elementary school in educational system of Iran - seyed mahdi hosseini; kourosh fathiVajargah; mahmoud haghani; mahboobeh arefi; Morteza Rezaeezadeh (Shahid Chamran University of Ahvaz, 2021)
Introduction As technology has grown, so problems related to its use raised. Because the growth of technology has increased the availability and expansion of the use of technology in primary schools as well as the use of these technologies by students at home, so the need to support students to stay safe, accountable, participate and collaboration in cyberspace and the like is more than ever. Issues related to the expansion of the use of technology and cyberspace; necessitate the education of digital citizens by the educational system.Method The purpose of this study was to investigate the position of digital citizenship education in the official curricula of elementary school in Iran. This research was descriptive and included documentary analysis and content analysis by Shannon entropy method. Content Analysis Unit; It was texts, pictures and textbook activities. The statistical population of the study was 41 volumes of elementary school textbooks in the academic year 2019-2020, of which 24 volumes were selected by purposive sampling. To determine the validity of the instrument, content validity was used in the form of a survey of experts on the degree of coordination of the content of the measuring instrument and the purpose of the research. The reliability coefficient was obtained by Scott method 0.83. ResultsFindings showed that out of 2631 counting units counted; 98 cases were related to the eight components of digital citizenship education. In other words, about 4% of the content of the three sections of the content of the studied textbooks has paid attention to the desirable components of digital citizenship education.Findings from Shannon entropy analysis showed that the highest Ej and Wj among the components of digital citizenship education belong to the component of "digital literacy" with a total value of (0.3866) and the lowest Ej and Wj belong to the components of "digital Security", "digital Etiquette", "digital Rights and Responsibilities", "digital laws" and "digital commerce " all to the value of (0).DiscussionAccording to the findings, it can be concluded that the position of digital citizenship education in Iranian elementary school curricula has been largely neglected. Therefore, it is suggested that considering the necessity of educating digital citizens in the present age, elementary school curricula should be revised in terms of providing appropriate coverage on the components required for educating digital citizens.